2019
DOI: 10.1016/j.omtn.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

TraFo-CRISPR: Enhanced Genome Engineering by Transient Foamy Virus Vector-Mediated Delivery of CRISPR/Cas9 Components

Abstract: The adaptation of CRISPR/Cas technology for use in mammals has revolutionized genome engineering. In particular with regard to clinical application, efficient expression of Cas9 within a narrow time frame is highly desirable to minimize the accumulation of off-target editing. We developed an effective, aptamer-independent retroviral delivery system for Cas9 mRNAs that takes advantage of a unique foamy virus (FV) capability: the efficient encapsidation and transfer of non-viral RNAs. This enabled us to create a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 88 publications
1
21
0
Order By: Relevance
“…[73][74][75][76][77] The possible reasons are the heterogeneity of T cells and tumor cells and their complex interactions in the tumor microenvironment. [78][79][80][81] Immunogenomics is a relatively new field of cancer research. The detection and analysis of whole-genome sequencing (WGS), whole-exome sequencing (WES), and RNA sequencing (RNA-Seq) on T cells and tumor cells by NGS technology can obtain genome maps of tumors and immune cells, which can help to customize treatment schemes for specific characteristics of tumors and increase the possibility of success.…”
Section: Next-generation Sequencing and Immunotherapy For Tumorsmentioning
confidence: 99%
“…[73][74][75][76][77] The possible reasons are the heterogeneity of T cells and tumor cells and their complex interactions in the tumor microenvironment. [78][79][80][81] Immunogenomics is a relatively new field of cancer research. The detection and analysis of whole-genome sequencing (WGS), whole-exome sequencing (WES), and RNA sequencing (RNA-Seq) on T cells and tumor cells by NGS technology can obtain genome maps of tumors and immune cells, which can help to customize treatment schemes for specific characteristics of tumors and increase the possibility of success.…”
Section: Next-generation Sequencing and Immunotherapy For Tumorsmentioning
confidence: 99%
“…Indeed, the titers we obtained with these vector batches remained high, and they are in the best design configuration for efficient gene editing. Other groups used similar bacteriophage systems to create particles that can transfer RNA into target cells using a slightly different design compared with ours [ 15 , 18 , 19 ]. Briefly, Knopp et al replaced the nucleocapsid by a genetically fused MS2 heterodimer to generate non-integrating gammaretroviral murine leukemia virus-based CRISPR/Cas9 all-in-one particles.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of the foamy viruses to efficiently package non-viral cellular RNAs [ 86 , 87 ], Lindel et al successfully used foamy viral capsid to package and deliver SpCas9 mRNA [ 49 ]. They observed > 80% genome editing activity and improved specificity compared with viral delivery.…”
Section: Using Vlps As Safe Gene Editing Delivery Vehiclesmentioning
confidence: 99%
“…So far, VLP-mediated Cas9 mRNA delivery to mammalian cells was more successful than sgRNA delivery. Several studies have found that sgRNA packaged alone could not be functionally delivered [ 47 , 49 , 55 ]. Single guide RNA is very unstable in cells unless complexed with Cas9 protein [ 88 ].…”
Section: Using Vlps As Safe Gene Editing Delivery Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation